2016
DOI: 10.1002/2016ja022635
|View full text |Cite
|
Sign up to set email alerts
|

Structuring of intermediate scale equatorial spread F irregularities during intense geomagnetic storm of solar cycle 24

Abstract: Here we examine the structuring of equatorial plasma bubble (EPB) during intense geomagnetic storm of solar cycle (SC) 24 that occurred on 17 March 2015 using spaced receiver scintillation observations on a 251 MHz radio signal, recorded by a network of stations in Indian region. As yet, this is the strongest geomagnetic storm (Dstmin∼−223nT) that occurred in present SC. Present study reveals that the structuring of equatorial spread F (ESF) irregularities was significantly different on 17 March as compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 48 publications
4
29
0
Order By: Relevance
“…As seen in section 3, very strong kilometer‐scale irregularities with a steep irregularity spectrum give rise to focusing of the VHF radio signal yielding S 4 indices >1. In the month of March 2015, VHF scintillation events were recorded at the equatorial station TIR with S 4 >1 during some part of the night on 23 nights, while for the same VHF signal recorded at MUM, which is located close to the crest of the EIA, S 4 indices close to 1 were observed during those events, but S 4 did not exceed 1 [ Kakad et al ., ]. This indicated that the spectrum of irregularities that mapped down from an altitude of 500 km above the geomagnetic equator to the IPP for MUM at 300 km altitude must have a shallow spectrum compared to the spectrum of irregularities near the equatorial F peak.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As seen in section 3, very strong kilometer‐scale irregularities with a steep irregularity spectrum give rise to focusing of the VHF radio signal yielding S 4 indices >1. In the month of March 2015, VHF scintillation events were recorded at the equatorial station TIR with S 4 >1 during some part of the night on 23 nights, while for the same VHF signal recorded at MUM, which is located close to the crest of the EIA, S 4 indices close to 1 were observed during those events, but S 4 did not exceed 1 [ Kakad et al ., ]. This indicated that the spectrum of irregularities that mapped down from an altitude of 500 km above the geomagnetic equator to the IPP for MUM at 300 km altitude must have a shallow spectrum compared to the spectrum of irregularities near the equatorial F peak.…”
Section: Discussionmentioning
confidence: 99%
“…The promptly penetrated eastward electric field around dusk added to the postsunset PRE eastward electric field in the equatorial ionosphere caused h ′ F at TIR on 17 March 2015 to be raised by ~150 km around 20 IST compared to h ′ F on 13 March 2015. This resulted in faster development of EPBs in the F region over TIR [ Basu et al ., ; Kakad et al ., ], the EPBs extended to greater altitudes over the geomagnetic equator and as a result mapped down to higher latitudes. This can be seen from Figure , where plots of S 4 for scintillations on the 251 MHz signal recorded at all the four VHF receiver stations on 17 March 2015, and for scintillations on a 1.575 GHz signal transmitted from the geostationary satellite GSAT‐10 and recorded at L‐band receiver stations for which the signal path elevation angle was at least 55°, are shown as a function of IST in Figures a and b.…”
Section: Structuring Of Epb On a Magnetically Disturbed Nightmentioning
confidence: 99%
“…Through simulation, Keskinen et al () have demonstrated that the evolution of EPBs are considerably different during Q‐ and D‐days. The structuring of EPBs in the postsunset hours during magnetically active periods was found to be significantly different resulting in severe amplitude scintillations on VHF signal (Kakad et al, ). This was attributed to the disturbed time modulation of ambient eastward electric field that resulted in very large upward vertical drifts, which influenced the growth and evolution of RT plasma instability.…”
Section: Introductionmentioning
confidence: 99%
“…This storm surprised many space weather specialists since it took place without any significant precursor X-or M-type solar flares [Kamide and Kusano, 2015]. Due to its peculiar behavior, it has also immediately attracted the attention of the equatorial aeronomy community and several observational results illustrating its effects on the Earth's ionosphere-thermosphere system have already been reported in the literature [e.g., Zhang et al, 2015;Astafyeva et al, 2015;Ramsingh et al, 2015;Carter et al, 2016;Kakad et al, 2016;Zhong et al, 2016;Fagundes et al, 2016;Liu et al, 2016;Nava et al, 2016].…”
Section: Introductionmentioning
confidence: 99%